Stage design / Ismail Suleiman - Suleiman, Ismail (Faculty of Architecture, Planning and Surveying, 1982)
This research report is intended for all those who seek information on method of design, decoration and construction for the stage. The layout of the report is straightforwards: divided into six major topics, it starts from the basic design of stage and proceeds gradually to construction, decoration and all the technical requirements for the stage. The topics (1) Acting area, types of stage design, stage planning. (2) Backstage operation. (3) Stage scenery. (4) Stage machinery: -on the stage floor. -in the flies. (5) Stage lighting. (6) Examples are also given taken from overseas and also from local examples…